Reinforcing the poly(silylene arylacetylene)s via strong π-π stacking interactions. (16th August 2021) - Ma, Manping; Dai, Nipin; Liu, Xiaotian; Li, Chuan; Yuan, Qiaolong; Huang, Farong
Abstract: Silicon-containing arylacetylene resins show a trade-off between mechanical property and heat resistance as usual. A strategy is proposed by utilizing the interchain π-π stacking interactions to obtain a resin with both high mechanical property and heat resistance. In this work, silicon-containing arylacetylene resins separately with 2, 5-diphenyl- [1, 3, 4]-oxadiazole unit as π-π stacking precursors (PODSA-MM, PODSA-MP) and the phenylene unit (PESA-MM, PESA-MP) in the main chains were synthesized by Grignard reactions. The stronger interchain π-π stacking interactions in the PODSA resins compared with PESA resins were confirmed by UV–Vis, XRD, SAXS analyses, regardless of whether or not the resins are cured. The PODSA resins with more regular structures show higher melting temperature and melt viscosity. The stable physical and chemical crosslinking dual-networks caused by both strong interchain interactions and thermal crosslinking reactions are formed in cured PODSA resins. The cured PODSA resins exhibit higher secondary relaxation temperature ( T β ), mechanical properties and thermal conductivity than cured PESA resins. The enhancement of properties of the cured PODSA resins are mainly attributed to stronger intermolecular π-π stacking interactions derived from 2, 5-diphenyl- [1, 3, 4]-oxadiazole unit. Graphical abstract: Image 1 Highlights: PODSA resins have stronger interchain π-π stacking interactions than PESA resins. The stable physical and chemical crosslinking dual-networks formed after curing. The cured PODSA resins show high T β, mechanical properties and thermal conductivity.